Improving Creativity through Workforce Diversity: A Case of Higher Education Institutions of Khyber Pakhtunkhwa - Haleem, Fazal; Khalil Ur Rahman (Journal of Business & Tourism, 2023)
This study empirically tests the impact of workforce diversity on creativity among teaching faculties of universities in Khyber Pakhtunkhwa. Employing a convenient sampling technique, a sample of 180 employees - Lecturers, Assistant Professors, Associate Professors, and Professors of the universities - is collected from the universities situated in Khyber Pakhtunkhwa. A total of 180 questionnaires were disseminated among the respondents out of which 160 appropriate questionnaires were received forming a percentage of 88.8%. Multiple analyses descriptive statistics, reliability analysis, correlation analysis and regression analysis are conducted to make sure the findings are reliable and meet the scientific rigor. The results of the research reveal that workforce diversity as a whole and its dimensions Age diversity, Gender diversity and Education diversity have significant impact on creativity. This implies that the administration of the universities should make sure to induce diversity in their workforce to enhance learning, teaching, and research as well as enrich the students’ experience.